2020
DOI: 10.1080/14712598.2020.1789097
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pneumonia and immune-related pneumonitis: critical issues on differential diagnosis, potential interactions, and management

Abstract: Introduction: The COVID-19 pandemic occurred amid the cancer immunotherapy revolution. Immune checkpoint inhibitors (ICIs) have become the standard of care for several solid cancers and are associated with peculiar toxicities, including pneumonitis which has similar features to COVID-19 pneumonia. Areas covered: We summarize the main hallmarks of lung injury induced by ICIs and severe acute respiratory syndrome coronavirus 2 and discuss the critical aspects for differential diagnosis and management. Symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Other analyses suffered from a small sample size (23). The large-scale proteomics analysis's primary goal is to deliver clues to potential mechanisms leading to disease pathology, especially if combined with longitudinal analysis of marker dynamics (1,11,23,24). However, such studies generate large amounts of data that are often difficult to put in the context of illness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other analyses suffered from a small sample size (23). The large-scale proteomics analysis's primary goal is to deliver clues to potential mechanisms leading to disease pathology, especially if combined with longitudinal analysis of marker dynamics (1,11,23,24). However, such studies generate large amounts of data that are often difficult to put in the context of illness.…”
mentioning
confidence: 99%
“…The treatments in COVID-19 should modulate the direct viral cytotoxicity and immune system response to infection (7,28,29). The ideal therapy for viral septicemia should reverse immune dysfunctions, normalize immunological mediators, and reverse organ failures (7,11,24). However, it is unclear how any proposed treatments for COVID-19 would alter the immunological reaction in the yet-to-be-described immunological landscape of the COVID-19 disease.…”
mentioning
confidence: 99%
“…Additionally, a “transfer learning” strategy, including some ICI patients’ CT data, should be tested and adapted for the partial training of algorithms. This is particularly important, as COVID-19 pneumonia cases are expected to decrease in the future and might become epidemiologically less relevant with the development and distribution of adequate vaccination therapies, whereas the number of ICI therapy-related pneumonitis is predicted to increase according to the increasing usage of ICI in cancer patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, recent reports have suggested that COVID-19 infection may mask ICI-related pneumonitis symptoms, thus potentially delaying essential treatments. [7,35] Although this might be detrimental considering that ICI-related pneumonitis accounts for about one-third of treatment-related deaths, their incidence is relatively rare. Furthermore, the risks of ICI pneumonitis tend to be augmented in early ICI recipients and super-responders [36], suggesting that a prompt and accurate risk strati cation, in addition to increased COVID-19 vigilance, may be able to mitigate this issue.…”
Section: Discussionmentioning
confidence: 99%